Forming of protein bubbles and porous films using co-axial electrohydrodynamic flow processing - Ekemen, Z; Ahmad, Z; Edirisinghe, M; Stride, E (2011)
Air and 5 wt.-% BSA solution are used as a model system to generate protein-coated microbubbles, which are significantly smaller in diameter than the processing needle apertures. The effects of processing parameters (applied voltage and flow rate) on the bubble size distribution and stability are studied. The optimal processing conditions are also explored in terms of heating of the solutions and prepared structures. Both individual microbubbles and porous films were successfully prepared using this method which has significant potential for the preparation of microbubbles for drug delivery systems, porous coatings, thin films, scaffolds and ultrasound contrast agents. The versatile nature of the method implies that many macromolecules and other active agents can be used. Microbubbles using a model protein (BSA) as the coating material were generated using co-axial electrohydrodynamic flow. The polydispersity index (PI) of these bubbles was controlled by careful modification of the processing parameters and the solution properties. Under optimal conditions, which results in a low PI, protein bubbles can be used to prepare porous and layered structures or be used as standalone agent carriers. Copyright © 2011 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.